Violencia intrafamiliar y su incidencia en el comportamiento de los alumnos de sexto año de educación básica de la Escuela Dr. Modesto Chávez Franco de la parroquia Torata del cantón Santa Rosa, en el periodo 2012-2013. - Ruales Ochoa, Leydi Isabel (2013)
The problem is wrapped in as a parent have suffered violence since childhood because children have low formation of personality and are very susceptible to abuse which also in some cases their characters change and are aggressive.